Research genres and multiliteracies: channelling the audience's gaze in powerpoint presentations - Nascimento, Roseli Gonçalves do (2012)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.